A composite proton exchange membrane for all-vanadium liquid flow battery and a preparation method thereof
By introducing fluorine groups and sulfonic acid groups modified carbon nanotubes into the proton exchange membrane of all vanadium flow batteries, the problem of vanadium ion shuttle is solved and the coulombic efficiency and energy efficiency of the battery are improved.
Patent Information
- Application Number
- CN202411413962.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The proton exchange membrane of existing all-vanadium flow batteries is difficult to effectively prevent vanadium ions from shuttled, while maintaining proton transmission capabilities, resulting in a decrease in battery capacity and inefficiency.
The corrosion-resistant perfluorosulfonic acid resin or sulfonated polyether ether ketone resin is used as the matrix to introduce hyperbranched polyethylene modified oligowalled carbon nanotubes containing fluorine groups and sulfonic acid groups at the end to enhance the proton transport capability of the proton exchange membrane and hinder the shuttle of vanadium ions.
Effectively hinder vanadium ions shuttle, improve the balun efficiency and energy efficiency of the battery, reduce membrane impedance, and improve voltage efficiency.
Smart Images

Figure CN118930927B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of all-vanadium liquid flow battery diaphragms, and in particular relates to a composite proton exchange membrane for an all-vanadium liquid flow battery and a preparation method thereof. Background Art
[0002] All-vanadium liquid flow battery has become one of the more mature long-term electrochemical energy storage technologies with its advantages of high safety, strong power and capacity scalability, long service life, and no cross-contamination of positive and negative electrolytes. It can better meet the application needs of new energy consumption, peak load regulation and frequency regulation. All-vanadium liquid flow battery uses dilute sulfuric acid aqueous solution of vanadium ions as energy storage medium, and realizes the mutual conversion of electrical energy and chemical energy through the rise and fall of the valence state of vanadium ions in the positive and negative electrolytes. When charging, the positive electrode VO 2+ Lose electrons and convert to VO 2+ , negative electrode V 3+ Gain electrons and convert them into V 2+ During the charge and discharge process, the ion valence states of the positive electrode VO 2 + , VO 2+ and negative electrode V 3+ 、V 2+ The proton exchange membrane is used to isolate the vanadium ion active material from the positive and negative electrodes to prevent self-discharge and reduce the battery capacity. On the other hand, the protons in the electrolyte can be transmitted between the positive and negative electrodes through the proton exchange membrane to close the charge and discharge circuit. Therefore, the ideal proton exchange membrane in the all-vanadium liquid flow battery needs to completely block the passage of vanadium ions and only allow a large number of protons to shuttle back and forth.
[0003] Considering VO 2+ It has strong corrosiveness. The currently commonly used proton exchange membrane is mainly a perfluorosulfonic acid membrane, which is composed of a highly corrosion-resistant perfluorocarbon main chain and a sulfonic acid group side chain with proton conductivity. However, the size of the hydrophilic proton conduction phase region composed of sulfonic acid groups and water molecules is much larger than the diameter of hydrated vanadium ions, resulting in vanadium ion shuttling, but reducing the sulfonic acid group content will weaken the proton conduction ability. Therefore, the development of a proton exchange membrane that can reduce vanadium ion shuttling and maintain proton transmission ability has become a problem that needs to be solved at present. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned prior art, the present invention provides a proton exchange membrane for an all-vanadium liquid flow battery and a preparation method thereof. The membrane uses a perfluorosulfonic acid resin or a sulfonated polyetheretherketone resin with strong corrosion resistance as a matrix, and introduces a few-layer carbon nanotubes modified with hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends, which hinders the shuttling of vanadium ions and enhances the proton transmission capacity of the proton exchange membrane.
[0005] The present invention adopts the following technical solution:
[0006] A composite proton exchange membrane for an all-vanadium liquid flow battery and a preparation method thereof, comprising the following steps:
[0007] S1: 1-3 parts by weight of hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends and 1-3 parts by weight of multi-walled carbon nanotubes are added to 200 parts by weight of a solvent, and ultrasonicated for 48-96 hours to obtain a mixed solution. After the mixed solution is centrifuged at a low speed, the upper layer liquid is taken out, and the upper layer liquid is centrifuged at a high speed to obtain a precipitate. The precipitate is added to 50 parts by weight of a solvent, ultrasonicated for 30 minutes, and then centrifuged. The ultrasonic-centrifugation operation is repeated 3-5 times, and the precipitate is ultrasonically dispersed in the solvent to obtain a dispersion of oligo-walled carbon nanotubes;
[0008] S2: dissolving 500 parts by mass of resin powder into 5000 parts by mass of solvent, then adding 1-5 parts by mass of oligo-walled carbon nanotube dispersion, stirring at 500-1000 rpm for 0.5-2 h to mix the solution evenly, and then ultrasonicating for 0.5-4 h to obtain a mixed solution;
[0009] S3: pouring the mixed solution onto the surface of the silicon wafer for spin coating, and obtaining a composite proton exchange membrane after drying.
[0010] Preferably, the preparation method of the hyperbranched polyethylene containing a fluorine group and a sulfonic acid group at the end is:
[0011] (a) under ethylene protection, 26 parts by mass of anhydrous dichloromethane, 2 parts by mass of a bromine-containing monomer, 5-10 parts by mass of a 2-acrylamido-2-methyl-1-propane sulfonic acid monomer, and 0.2 parts by mass of a palladium catalyst are sequentially added into a reaction bottle, stirred and dissolved, the ethylene pressure is adjusted to 0.1-1 MPa, and the reaction is carried out at 25° C. for 12-24 hours. After the reaction is completed, the ethylene supply is stopped, and the anhydrous solvent is removed by cold blowing and purging to obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene containing bromine groups and sulfonic acid groups grafted thereon is obtained;
[0012] (b) 2 parts by mass of hyperbranched polyethylene grafted with bromine groups and sulfonic acid groups, 40-60 parts by mass of fluorine-containing monomers, and 1 part by mass of bipyridine are added to 100 parts by mass of anhydrous toluene, and the mixture is frozen with liquid nitrogen and then evacuated. Nitrogen is introduced, and under nitrogen protection, 1 part by mass of cuprous bromide is added, and the temperature is raised to 80° C. to start the reaction. After reacting for 4-12 hours, the reaction dispersion is separated and purified to obtain a hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends.
[0013] Preferably, the bromine-containing monomer includes at least one of 2-bromoisobutyryl bromide and 2-(2-bromoisobutyryloxy)ethyl methacrylate; the fluorine-containing monomer includes at least one of tetrafluoropropyl methacrylate, nonafluorohexyl methacrylate and dodecafluoroheptyl methacrylate.
[0014] Preferably, in step S1 and step S2, the solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0015] Preferably, in step S1, the rotation speed of the low-speed centrifugation is 2000-4000 rpm, and the time of the low-speed centrifugation is 20-60 min; the rotation speed of the high-speed centrifugation is 8000-12000 rpm, and the time of the high-speed centrifugation is 10-30 min.
[0016] Preferably, in step S1, the concentration of the oligo-walled carbon nanotube dispersion is 1-5 mg / mL.
[0017] Preferably, in step S2, the resin powder includes at least one of perfluorosulfonic acid resin and sulfonated polyetheretherketone resin.
[0018] Preferably, in step S3, the spin coating speed is 200-800 rpm, the spin coating time is 1-10 min; the drying temperature is 80-120° C., and the drying time is 8-12 h.
[0019] A composite proton exchange membrane for an all-vanadium liquid flow battery is prepared by using any of the above-mentioned methods for preparing a composite proton exchange membrane for an all-vanadium liquid flow battery.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention introduces hyperbranched polyethylene containing long chains of fluorine groups and sulfonic acid groups at the ends to prepare and in-situ modify carbon nanotubes. The fluorine groups and sulfonic acid groups have good compatibility with the resin matrix, making the carbon nanotubes more evenly dispersed in the matrix, better hindering the shuttle of vanadium ions, and improving the coulombic efficiency of the battery.
[0022] 2. The present invention introduces more sulfonic acid groups into the resin matrix through the hyperbranched polyethylene containing sulfonic acid groups at the end, thereby improving the proton transmission capacity, reducing the membrane impedance, and improving the voltage efficiency and energy efficiency of the battery.
[0023] 3. The present invention introduces carbon nanotubes modified with sulfonic acid groups, so that hydrated protons form hydrated proton clusters and short proton transport channels on the surface of carbon nanotubes, thereby improving the proton transport efficiency of the proton exchange membrane and the voltage efficiency and energy efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of a method for preparing a composite proton exchange membrane for an all-vanadium liquid flow battery according to the present invention;
[0025] Figure 2 This is a transmission electron microscope image of the oligo-walled carbon nanotubes prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the present invention are not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] like Figure 1 As shown, a composite proton exchange membrane for an all-vanadium liquid flow battery and a preparation method thereof, comprising the following steps:
[0028] S1: 1-3 parts by weight of hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the end and 1-3 parts by weight of multi-walled carbon nanotubes are added to 200 parts by weight of solvent, and ultrasonicated for 48-96 hours to obtain a mixed solution, and the mixed solution is centrifuged at a low speed, and the upper layer liquid is taken out, and the upper layer liquid is centrifuged at a high speed to obtain a precipitate, and the precipitate is added to 50 parts by weight of solvent, ultrasonicated for 30 minutes, and then centrifuged, and the ultrasonic-centrifugation operation is repeated 3-5 times, and the precipitate is ultrasonically dispersed in the solvent to obtain an oligo-walled carbon nanotube dispersion; The preparation method of hyperbranched polyethylene is as follows: (a) under ethylene protection, 26 parts by weight of anhydrous dichloromethane, 2 parts by weight of a bromine-containing monomer, 5 to 10 parts by weight of a 2-acrylamido-2-methyl-1-propane sulfonic acid monomer, and 0.2 parts by weight of a palladium catalyst are sequentially added into a reaction bottle, stirred and dissolved, the ethylene pressure is adjusted to 0.1 to 1 MPa, and the reaction is carried out at 25° C. for 12 to 24 hours. After the reaction is completed, the ethylene supply is stopped, and the anhydrous solvent is removed by cold blowing and purging to obtain a saturated preliminary product. After separation and purification, a product containing Hyperbranched polyethylene grafted with bromine groups and sulfonic acid groups; (b) adding 2 parts by weight of hyperbranched polyethylene grafted with bromine groups and sulfonic acid groups, 40-60 parts by weight of fluorine-containing monomers, and 1 part by weight of bipyridine to 100 parts by weight of anhydrous toluene, freezing with liquid nitrogen and then evacuating, introducing nitrogen, adding 1 part by weight of cuprous bromide under nitrogen protection, heating to 80°C to start the reaction, reacting for 4-12 hours, separating and purifying the reaction dispersion to obtain a hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends; the bromine-containing monomers include 2 -bromoisobutyryl bromide, 2-(2-bromoisobutyryloxy)ethyl methacrylate; the fluorine-containing monomer includes at least one of tetrafluoropropyl methacrylate, nonafluorohexyl methacrylate, and dodecafluoroheptyl methacrylate; the speed of low-speed centrifugation is 2000-4000 rpm, and the time of low-speed centrifugation is 20-60 min; the speed of high-speed centrifugation is 8000-12000 rpm, and the time of high-speed centrifugation is 10-30 min; the concentration of the oligo-walled carbon nanotube dispersion is 1-5 mg / mL;
[0029] S2: dissolving 500 parts by mass of resin powder into 5000 parts by mass of solvent, then adding 1-5 parts by mass of oligo-walled carbon nanotube dispersion, stirring at a high speed of 500-1000 rpm for 0.5-2 hours to mix the solution evenly, and then ultrasonicating for 0.5-4 hours to obtain a mixed solution; the resin powder includes at least one of perfluorosulfonic acid resin and sulfonated polyetheretherketone resin;
[0030] S3: pouring the mixed solution onto the surface of the silicon wafer for spin coating, and obtaining a composite proton exchange membrane after drying; the spin coating speed is 200-800 rpm, the spin coating time is 1-10 min; the drying temperature is 80-120° C., and the drying time is 8-12 h;
[0031] In step S1 and step S2, the solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone;
[0032] A composite proton exchange membrane for an all-vanadium liquid flow battery is prepared by using any of the above-mentioned methods for preparing a composite proton exchange membrane for an all-vanadium liquid flow battery.
[0033] Embodiment 1: comprises the following steps:
[0034] S1: Under ethylene protection, 26g of anhydrous dichloromethane, 2g of 2-(2-bromoisobutyryloxy)ethyl methacrylate monomer, 5g of 2-acrylamido-2-methyl-1-propanesulfonic acid monomer, and 0.2g of palladium catalyst were added into the reaction bottle in sequence, stirred and dissolved, and the ethylene pressure was adjusted to 0.1MPa. The reaction was carried out at 25°C for 24h. After the reaction was completed, the ethylene supply was stopped, and the anhydrous dichloromethane was removed by cold blowing to obtain a saturated preliminary product. After separation and purification, a hyperbranched product containing bromine groups and sulfonic acid groups grafted was obtained. Polyethylene; 2g of hyperbranched polyethylene grafted with bromine groups and sulfonic acid groups, 40g of tetrafluoropropyl methacrylate monomer, and 1g of bipyridine are added to 100g of anhydrous toluene, and the mixture is frozen with liquid nitrogen and then vacuumized, and nitrogen is introduced. Under nitrogen protection, 1g of cuprous bromide is added, and the temperature is raised to 80°C to start the reaction. After reacting for 4h, the reaction dispersion is separated and purified to obtain a hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends; 1g of hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends and 1g of multi-walled carbon nanotubes are added to 200g of N ,N-dimethylformamide, ultrasonically perform 48 hours to obtain a mixed solution, centrifuge the mixed solution at 4000 rpm for 20 minutes, take out the upper layer, and centrifuge the upper layer at 8000 rpm for 30 minutes to obtain a precipitate, add the precipitate to 50gN,N-dimethylformamide, ultrasonically perform 30 minutes, and then centrifuge, repeat the ultrasonic-centrifugation operation 5 times, and ultrasonically disperse the precipitate in N,N-dimethylformamide to obtain a dispersion of oligo-walled carbon nanotubes with a concentration of 1 mg / mL;
[0035] S2: 50 g of perfluorosulfonic acid resin powder was dissolved in 500 g of N,N-dimethylformamide, and then 0.1 g of oligo-walled carbon nanotube dispersion was added, and the solution was stirred at 500 rpm for 2 h to mix the solution evenly, and then ultrasonicated for 0.5 h to obtain a mixed solution;
[0036] S3: pouring the mixed solution onto the surface of the silicon wafer for spin coating at a spin coating speed of 200 rpm for 10 min, and drying at 80° C. for 12 h to obtain a composite proton exchange membrane;
[0037] Figure 2 This is a transmission electron micrograph of the oligo-walled carbon nanotubes prepared in this example. It can be observed that under the assisted exfoliation of the hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends, the oligo-walled carbon nanotubes are evenly dispersed in the dispersion without obvious entanglement. The length of the oligo-walled carbon nanotubes is 0.1 μm to 0.2 μm.
[0038] Embodiment 2: comprises the following steps:
[0039] S1: Under ethylene protection, 26g of anhydrous dichloromethane, 2g of 2-(2-bromoisobutyryloxy)ethyl methacrylate monomer, 7.5g of 2-acrylamido-2-methyl-1-propanesulfonic acid monomer, and 0.2g of palladium catalyst were added to the reaction bottle in sequence, stirred and dissolved, and the ethylene pressure was adjusted to 0.5MPa. The reaction was carried out at 25°C for 18h. After the reaction was completed, the ethylene supply was stopped, and the anhydrous dichloromethane was removed by cold blowing to obtain a saturated preliminary product. After separation and purification, a hyperbranched product containing bromine groups and sulfonic acid groups grafted was obtained. polyethylene; 2g of hyperbranched polyethylene grafted with bromine groups and sulfonic acid groups, 50g of tetrafluoropropyl methacrylate monomer, and 1g of bipyridine were added to 100g of anhydrous toluene, and the mixture was frozen with liquid nitrogen and then vacuumized, and nitrogen was introduced. Under nitrogen protection, 1g of cuprous bromide was added, and the temperature was raised to 80°C to start the reaction. After the reaction was carried out for 8h, the reaction dispersion was separated and purified to obtain a hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends; 2g of hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends, and 2g of multi-walled carbon nanotubes were added to 200g of N ,N-dimethylformamide, ultrasonically perform 72h to obtain a mixed solution, centrifuge the mixed solution at 3000rpm for 40min, take out the upper layer, centrifuge the upper layer at 10000rpm for 20min to obtain a precipitate, add the precipitate to 50gN,N-dimethylformamide, ultrasonically perform 30min and then centrifuge, repeat the ultrasonic-centrifugation operation 4 times, ultrasonically disperse the precipitate in N,N-dimethylformamide to obtain a 3mg / mL oligo-walled carbon nanotube dispersion;
[0040] S2: Dissolve 50 g of perfluorosulfonic acid resin powder in 500 g of N,N-dimethylformamide, then add 0.1 g of oligo-walled carbon nanotube dispersion, stir at 700 rpm for 1 h to mix the solution evenly, and then ultrasonicate for 2 h to obtain a mixed solution;
[0041] S3: Pour the mixed solution onto the surface of the silicon wafer for spin coating at a spin coating speed of 300 rpm for 5 min. Dry at 100° C. for 10 h to obtain a composite proton exchange membrane.
[0042] Embodiment 3: comprises the following steps:
[0043] S1: Under ethylene protection, 26g of anhydrous dichloromethane, 2g of 2-(2-bromoisobutyryloxy)ethyl methacrylate monomer, 10g of 2-acrylamido-2-methyl-1-propanesulfonic acid monomer, and 0.2g of palladium catalyst were added into the reaction bottle in sequence, stirred and dissolved, and the ethylene pressure was adjusted to 1MPa. The reaction was carried out at 25°C for 12h. After the reaction was completed, the ethylene supply was stopped, and the anhydrous dichloromethane was removed by cold blowing to obtain a saturated preliminary product. After separation and purification, a hyperbranched polymer containing bromine groups and sulfonic acid groups grafted was obtained. ethylene; 2g of hyperbranched polyethylene grafted with bromine groups and sulfonic acid groups, 60g of tetrafluoropropyl methacrylate monomer, and 1g of bipyridine were added to 100g of anhydrous toluene, and the mixture was frozen with liquid nitrogen and then vacuumized. Nitrogen was introduced, and 1g of cuprous bromide was added under nitrogen protection. The temperature was raised to 80°C to start the reaction. After reacting for 12 hours, the reaction dispersion was separated and purified to obtain a hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends; 3g of hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends, and 3g of multi-walled carbon nanotubes were added to 200gN ,N-dimethylformamide, ultrasonically perform 96 hours to obtain a mixed solution, centrifuge the mixed solution at 2000 rpm for 60 minutes, take out the upper layer, and centrifuge the upper layer at 12000 rpm for 10 minutes to obtain a precipitate, add the precipitate to 50gN,N-dimethylformamide, ultrasonically perform 30 minutes, and then centrifuge, repeat the ultrasonic-centrifugation operation 3 times, and ultrasonically disperse the precipitate in N,N-dimethylformamide to obtain a dispersion of oligo-walled carbon nanotubes with a concentration of 5 mg / mL;
[0044] S2: Dissolve 50 g of perfluorosulfonic acid resin powder in 500 g of N,N-dimethylformamide, then add 0.1 g of oligo-walled carbon nanotube dispersion, stir at 1000 rpm for 0.5 h to mix the solution evenly, and then ultrasonicate for 4 h to obtain a mixed solution;
[0045] S3: Pour the mixed solution onto the surface of the silicon wafer for spin coating at a spin coating speed of 800 rpm for 1 min, and dry at 120° C. for 8 h to obtain a composite proton exchange membrane.
[0046] Embodiment 4: comprises the following steps:
[0047] S1: Under ethylene protection, 26g of anhydrous dichloromethane, 2g of 2-bromoisobutyryl bromide monomer, 10g of 2-acrylamido-2-methyl-1-propane sulfonic acid monomer, and 0.2g of palladium catalyst were added into the reaction bottle in sequence, stirred and dissolved, and the ethylene pressure was adjusted to 0.1MPa. The reaction was carried out at 25°C for 24h. After the reaction was completed, the ethylene supply was stopped, and the anhydrous dichloromethane was removed by cold blowing to obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene containing bromine groups and sulfonic acid groups was obtained; 2 g of hyperbranched polyethylene grafted with bromine groups and sulfonic acid groups, 40 g of nonafluorohexyl methacrylate monomer, and 1 g of bipyridine were added to 100 g of anhydrous toluene, and the mixture was frozen with liquid nitrogen and then vacuumized. Nitrogen was introduced, and 1 g of cuprous bromide was added under nitrogen protection. The temperature was raised to 80°C to start the reaction. After the reaction was carried out for 8 hours, the reaction dispersion was separated and purified to obtain hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends; 1 g of hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends, and 3 g of multi-walled carbon nanotubes were added to 200 g of N ,N-dimethylacetamide, ultrasonically perform 96 hours to obtain a mixed solution, centrifuge the mixed solution at 4000 rpm for 40 minutes, take out the upper layer, and centrifuge the upper layer at 10000 rpm for 10 minutes to obtain a precipitate, add the precipitate to 50gN,N-dimethylacetamide, ultrasonically perform 30 minutes, and then centrifuge, repeat the ultrasonic-centrifugation operation 3 times, and ultrasonically disperse the precipitate in N,N-dimethylacetamide to obtain a dispersion of oligo-walled carbon nanotubes with a concentration of 1 mg / mL;
[0048] S2: Dissolve 50 g of perfluorosulfonic acid resin powder in 500 g of N,N-dimethylacetamide, then add 0.2 g of oligo-walled carbon nanotube dispersion, stir at 800 rpm for 1 h to mix the solution evenly, and then ultrasonicate for 2 h to obtain a mixed solution;
[0049] S3: Pour the mixed solution onto the surface of the silicon wafer for spin coating at a spin coating speed of 500 rpm for 3 min, and dry at 80° C. for 12 h to obtain a composite proton exchange membrane.
[0050] Embodiment 5: comprises the following steps:
[0051] S1: Under ethylene protection, 26g of anhydrous dichloromethane, 2g of 2-bromoisobutyryl bromide monomer, 10g of 2-acrylamido-2-methyl-1-propane sulfonic acid monomer, and 0.2g of palladium catalyst were added to the reaction bottle in sequence, stirred and dissolved, and the ethylene pressure was adjusted to 0.5MPa. The reaction was carried out at 25°C for 18h. After the reaction was completed, the ethylene supply was stopped, and the anhydrous dichloromethane was removed by cold blowing to obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene containing bromine groups and sulfonic acid groups was obtained; 2g of hyperbranched polyethylene containing bromine groups and sulfonic acid groups grafted, 50g of dodecafluoroheptyl methacrylate monomer, and 1g of bipyridine were added to 100g of anhydrous toluene, and vacuum was evacuated after freezing with liquid nitrogen, and nitrogen was introduced. Under protection, 1g of cuprous bromide was added, the temperature was raised to 80°C to start the reaction, and after the reaction for 8h, the reaction dispersion was separated and purified to obtain a hyperbranched polyethylene containing a fluorine group and a sulfonic acid group at the end; 2g of the hyperbranched polyethylene containing a fluorine group and a sulfonic acid group at the end and 3g of multi-walled carbon nanotubes were added to 200g of dimethyl sulfoxide, and ultrasonicated for 96h to obtain a mixed solution, the mixed solution was centrifuged at 4000rpm for 40min, the upper layer liquid was taken out, and the upper layer liquid was centrifuged at 10000rpm for 10min to obtain a precipitate, the precipitate was added to 50g of dimethyl sulfoxide, ultrasonicated for 30min, and then centrifuged, the ultrasonic-centrifugation operation was repeated 3 times, and the precipitate was ultrasonically dispersed in dimethyl sulfoxide to obtain a dispersion of oligo-walled carbon nanotubes with a concentration of 1mg / mL;
[0052] S2: 50 g of sulfonated polyetheretherketone resin powder was dissolved in 500 g of dimethyl sulfoxide, and then 0.4 g of oligo-walled carbon nanotube dispersion was added, and the solution was mixed evenly at 800 rpm for 1 h, and then ultrasonicated for 2 h to obtain a mixed solution;
[0053] S3: Pour the mixed solution onto the surface of the silicon wafer for spin coating at a spin coating speed of 700 rpm for 3 min, and dry at 80° C. for 12 h to obtain a composite proton exchange membrane.
[0054] Embodiment 6: comprises the following steps:
[0055] S1: Under ethylene protection, 26g of anhydrous dichloromethane, 2g of 2-bromoisobutyryl bromide monomer, 10g of 2-acrylamido-2-methyl-1-propane sulfonic acid monomer, and 0.2g of palladium catalyst were added to the reaction bottle in sequence, stirred and dissolved, and the ethylene pressure was adjusted to 1MPa. The reaction was carried out at 25°C for 12h. After the reaction was completed, the ethylene supply was stopped, and the anhydrous dichloromethane was removed by cold blowing to obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene containing bromine groups and sulfonic acid groups was obtained; 2g of hyperbranched polyethylene containing bromine groups and sulfonic acid groups, 60g of dodecafluoroheptyl methacrylate monomer, and 1g of bipyridine were added to 100g of anhydrous toluene, and the mixture was frozen with liquid nitrogen and then vacuumized. Nitrogen was introduced, and under nitrogen protection, 1 g cuprous bromide, heating to 80°C to start the reaction, after reacting for 8 hours, separating and purifying the reaction dispersion to obtain a hyperbranched polyethylene containing a fluorine group and a sulfonic acid group at the end; adding 3 g of the hyperbranched polyethylene containing a fluorine group and a sulfonic acid group at the end and 3 g of multi-walled carbon nanotubes to 200 g of N-methylpyrrolidone, ultrasonicating for 96 hours to obtain a mixed solution, centrifuging the mixed solution at 4000 rpm for 40 minutes, taking out the upper layer liquid, centrifuging the upper layer liquid at 10000 rpm for 10 minutes to obtain a precipitate, adding the precipitate to 50 g of N-methylpyrrolidone, ultrasonicating for 30 minutes and then centrifuging, repeating the ultrasonic-centrifugation operation 3 times, ultrasonically dispersing the precipitate in N-methylpyrrolidone to obtain a dispersion of oligo-walled carbon nanotubes with a concentration of 1 mg / mL;
[0056] S2: 50 g of sulfonated polyetheretherketone resin powder was dissolved in 500 g of N-methylpyrrolidone, and then 0.5 g of oligo-walled carbon nanotube dispersion was added, and the solution was mixed evenly at 800 rpm for 1 h, and then ultrasonicated for 2 h to obtain a mixed solution;
[0057] S3: Pour the mixed solution onto the surface of the silicon wafer for spin coating at a spin coating speed of 800 rpm for 1 min, and dry at 80° C. for 12 h to obtain a composite proton exchange membrane.
[0058] Comparative Example 1: comprising the following steps:
[0059] S1: Under ethylene protection, 26g of anhydrous dichloromethane, 2g of 2-(2-bromoisobutyryloxy)ethyl methacrylate monomer, and 0.2g of palladium catalyst were added to the reaction bottle in sequence, stirred and dissolved, the ethylene pressure was adjusted to 0.1MPa, and the reaction was carried out at 25°C for 24h. After the reaction was completed, the ethylene supply was stopped, and the anhydrous dichloromethane was removed by cold blowing to obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene containing a bromine group grafted was obtained; 2g of a hyperbranched polyethylene containing a bromine group grafted, 60g of tetrafluoropropyl methacrylate monomer, and 1g of bipyridine were added to 100g of anhydrous toluene, and the mixture was frozen with liquid nitrogen and then vacuumed, and nitrogen was introduced. Under nitrogen protection, 1g of cuprous bromide was added, and the temperature was raised to 80°C to start the reaction. After the reaction was carried out for 8h, the reaction dispersion was separated and purified to obtain a hyperbranched polyethylene containing a fluorine group at the end; 3g of a hyperbranched polyethylene containing a fluorine group at the end and 3g of multi-walled carbon nanotubes were added to 200gN ,N-dimethylformamide, ultrasonically perform 48 hours to obtain a mixed solution, centrifuge the mixed solution at 4000 rpm for 40 minutes, take out the upper layer, and centrifuge the upper layer at 10000 rpm for 10 minutes to obtain a precipitate, add the precipitate to 50gN,N-dimethylformamide, ultrasonically perform 30 minutes, and then centrifuge, repeat the ultrasonic-centrifugation operation 3 times, and ultrasonically disperse the precipitate in N,N-dimethylformamide to obtain a dispersion of oligo-walled carbon nanotubes with a concentration of 5 mg / mL;
[0060] S2: Dissolve 50 g of perfluorosulfonic acid resin powder in 500 g of N,N-dimethylformamide, then add 0.1 g of oligo-walled carbon nanotube dispersion, stir at 800 rpm for 1 h to mix the solution evenly, and then ultrasonicate for 2 h to obtain a mixed solution;
[0061] S3: Pour the mixed solution onto the surface of the silicon wafer for spin coating at a spin coating speed of 800 rpm for 1 min, and dry at 80° C. for 12 h to obtain a composite proton exchange membrane.
[0062] Comparative Example 2: comprising the following steps:
[0063] S1: 3 g of multi-walled carbon nanotubes were added to 200 g of N, N-dimethylformamide, and ultrasonicated for 96 h to obtain a mixed solution. The mixed solution was centrifuged at 4000 rpm for 40 min, the upper layer was taken out, and the upper layer was centrifuged at 10000 rpm for 10 min to obtain a precipitate. The precipitate was added to 50 g of N, N-dimethylformamide, ultrasonicated for 30 min, and then centrifuged. The ultrasonic-centrifugation operation was repeated 3 times, and the precipitate was ultrasonically dispersed in N, N-dimethylformamide to obtain a dispersion of oligo-walled carbon nanotubes with a concentration of 5 mg / mL;
[0064] S2: Dissolve 50 g of perfluorosulfonic acid resin powder in 500 g of N,N-dimethylformamide, then add 0.1 g of oligo-walled carbon nanotube dispersion, stir at 800 rpm for 1 h to mix the solution evenly, and then ultrasonicate for 2 h to obtain a mixed solution;
[0065] S3: Pour the mixed solution onto the surface of the silicon wafer for spin coating at a spin coating speed of 800 rpm for 1 min, and dry at 80° C. for 12 h to obtain a composite proton exchange membrane.
[0066] Comparative Example 3: comprising the following steps:
[0067] S1: Dissolve 500g of perfluorosulfonic acid resin powder in 5000g of N,N-dimethylformamide, stir at 800rpm for 1h to mix the solution evenly, and then ultrasonicate for 2h to obtain a mixed solution;
[0068] S2: Pour the mixed solution onto the surface of the silicon wafer for spin coating at a spin coating speed of 800 rpm for 1 min. Dry at 80° C. for 12 h to obtain a composite proton exchange membrane.
[0069] The all-vanadium redox flow batteries obtained in Examples 1-6 and Comparative Examples 1-3 were assembled into battery stacks using proton exchange membranes for battery performance testing, and the coulombic efficiency, voltage efficiency, and energy efficiency were recorded under the same test conditions. The test results are shown in Table 1:
[0070] Table 1 Battery performance test table of the battery stack assembled using the membranes of the embodiment and the comparative example
[0071]
[0072] As can be seen from Table 1, compared with Comparative Example 1, Examples 1 to 6 introduced sulfonic acid groups, showing that both voltage efficiency and energy efficiency were significantly improved, indicating that the hyperbranched polyethylene containing sulfonic acid groups at the end introduced more sulfonic acid groups in the resin matrix, improved proton transfer capacity, reduced membrane impedance, and improved battery voltage efficiency and energy efficiency; Compared with Comparative Example 2, Examples 1 to 6 introduced hyperbranched polyethylene containing long chains of fluorine groups and sulfonic acid groups at the end, showing that coulombic efficiency, voltage efficiency and energy efficiency were all improved, mainly because the hyperbranched polyethylene containing long chains of fluorine groups and sulfonic acid groups at the end increased the compatibility of the oligo-walled carbon nanotubes with the resin matrix, making the dispersion of the oligo-walled carbon nanotubes in the matrix more uniform, better hindering the shuttle of vanadium ions, and improving the coulombic efficiency of the battery. At the same time, the introduced sulfonic acid groups improve the proton transmission capacity, thereby increasing the voltage efficiency and energy efficiency of the battery; compared with Comparative Example 3, Comparative Example 2 introduces unmodified oligo-walled carbon nanotubes, showing an improvement in coulombic efficiency, but a decrease in voltage efficiency, indicating that oligo-walled carbon nanotubes can hinder the shuttling of vanadium ions and improve the coulombic efficiency of the battery, but due to the lack of sulfonic acid groups on the surface, the proton transmission capacity of the proton exchange membrane cannot be improved; compared with Comparative Examples 2 and 3, Examples 1 to 6 have greater voltage efficiency and energy efficiency, because the carbon nanotube surfaces introduced in Examples 1 to 6 contain modified sulfonic acid groups, so that hydrated protons form hydrated proton clusters and short proton transmission channels on the surface of the carbon nanotubes, thereby improving the proton transmission efficiency of the proton exchange membrane and improving the voltage efficiency and energy efficiency of the battery.
[0073] From the above detailed description of the embodiments of the present invention, it can be understood that the present invention provides a composite proton exchange membrane for an all-vanadium liquid flow battery and a preparation method thereof. By introducing carbon nanotubes modified with hyperbranched polyethylene containing long chains of fluorine groups and sulfonic acid groups at the ends, the dispersion of carbon nanotubes in the matrix can be improved, the shuttle of vanadium ions can be better hindered, and the coulombic efficiency of the battery can be improved. Sulfonic acid groups are introduced into the modified oligo-walled carbon nanotubes, and short proton transmission channels are formed on the surface, thereby improving the energy efficiency and voltage efficiency of the battery.
[0074] Although the preferred implementation of the present invention has been disclosed as above, it does not limit the present invention. Any technician in this field can make appropriate improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the claims.
Claims
1. A method for preparing a composite proton exchange membrane for an all-vanadium liquid flow battery, characterized in that: The steps include: S1: 1-3 parts by weight of hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends and 1-3 parts by weight of multi-walled carbon nanotubes are added to 200 parts by weight of solvent, and ultrasonicated for 48-96 hours to obtain a mixed solution. After the mixed solution is centrifuged at a low speed, the upper layer liquid is taken out, and the upper layer liquid is centrifuged at a high speed to obtain a precipitate. The precipitate is added to 50 parts by weight of solvent, ultrasonicated for 30 minutes, and then centrifuged. The ultrasonic-centrifugation operation is repeated 3-5 times, and the precipitate is ultrasonically dispersed in the solvent to obtain an oligo-walled carbon nanotube dispersion. The preparation method of the hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends is: (a) under ethylene protection, 26 parts by mass of anhydrous dichloromethane, 2 parts by mass of a bromine-containing monomer, 5-10 parts by mass of a 2-acrylamido-2-methyl-1-propane sulfonic acid monomer, and 0.2 parts by mass of a palladium catalyst are added to a reaction bottle in sequence, stirred and dissolved, the ethylene pressure is adjusted to 0.1-1 MPa, and the reaction is carried out at 25° C. for 12-24 hours. After the reaction is completed, the ethylene supply is stopped, and the anhydrous dichloromethane is removed by cold blowing and purging to obtain a saturated preliminary product. After separation and purification, a hyperbranched polyethylene containing bromine groups and sulfonic acid groups grafted thereon is obtained; (b) adding 2 parts by weight of hyperbranched polyethylene grafted with bromine groups and sulfonic acid groups, 40-60 parts by weight of fluorine-containing monomers, and 1 part by weight of bipyridine to 100 parts by weight of anhydrous toluene, freezing with liquid nitrogen, evacuating the mixture, introducing nitrogen, adding 1 part by weight of cuprous bromide under nitrogen protection, heating the mixture to 80° C. to start the reaction, reacting for 4-12 hours, separating and purifying the reaction dispersion to obtain a hyperbranched polyethylene containing fluorine groups and sulfonic acid groups at the ends; The bromine-containing monomer is at least one of 2-bromoisobutyryl bromide and 2-(2-bromoisobutyryloxy)ethyl methacrylate; the fluorine-containing monomer is at least one of tetrafluoropropyl methacrylate, nonafluorohexyl methacrylate, and dodecafluoroheptyl methacrylate; S2: dissolving 500 parts by mass of resin powder into 5000 parts by mass of solvent, then adding 1-5 parts by mass of oligo-walled carbon nanotube dispersion, stirring at a high speed of 500-1000 rpm for 0.5-2 hours to mix the solution evenly, and then ultrasonicating for 0.5-4 hours to obtain a mixed solution; the resin powder comprises at least one of perfluorosulfonic acid resin and sulfonated polyetheretherketone resin; S3: pouring the mixed solution onto the surface of the silicon wafer for spin coating, and obtaining a composite proton exchange membrane after drying.
2. The method for preparing a composite proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: In the step S1 and step S2, the solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
3. The method for preparing a composite proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: In step S1, the rotation speed of the low-speed centrifugation is 2000-4000 rpm, and the time of the low-speed centrifugation is 20-60 min; the rotation speed of the high-speed centrifugation is 8000-12000 rpm, and the time of the high-speed centrifugation is 10-30 min.
4. The method for preparing a composite proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: In the step S1, the concentration of the oligo-walled carbon nanotube dispersion is 1-5 mg / mL.
5. The method for preparing a composite proton exchange membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: In the step S3, the spin coating speed is 200-800 rpm, the spin coating time is 1-10 min; the drying temperature is 80-120° C., and the drying time is 8-12 h.
6. A composite proton exchange membrane for an all-vanadium liquid flow battery, characterized in that: The composite proton exchange membrane is prepared by the method for preparing a composite proton exchange membrane for an all-vanadium liquid flow battery according to any one of claims 1 to 5.
Citation Information
Patent Citations
Modified hyperbranched polymer (HBP), proton exchange membrane prepared by using same and preparation method of proton exchange membrane
CN101997125A
High-proton-conductivity high-strength perfluorosulfonic acid composite proton exchange membrane and preparation method thereof
CN113471496A